Solvency Analysis of PT Aneka Tambang Tbk. Before and During the Covid-19 Pandemic - Suryaningsum, Sri; Pamungkas, Noto; Jasmine, Jasmine; Harleyngton, Carlo (AIBPM Publisher, 2023)
This study aims to analyze the increase or decrease in the solvency ability of PT Aneka Tambang Tbk. This research is important to know the impact of the Covid-19 pandemic. The solvency ability of this study was measured by the Debt to Assets Ratio (DAR), Debt to Equity Ratio (DER), and Long Term Debt to Equity Ratio (LTDER). This research is included in a descriptive study with secondary data in the form of company financial statements for 2017-2021 which were obtained by literature and documentation studies. The analytical technique used in this research is a comparative descriptive analysis between years and also compares the average achievements of the industry. The results showed that there was an increase inÂ the compny's solvency ability during the Covid-19 pandemic when compared to the value of the DAR, DER, and LTDER ratios before the Covid-19 pandemic, this indicates that the Company is able to improve financial performance in the midst of a pandemic which has been considered the cause occurrence of a financial crisis. In addition, referring to the industry average, the company's DAR value is poor because it is above the average, while the DER and LTDER values are classified as good because they are below the industry average. The results of this study are expected to be developed by further researchers and used as consideration for related parties.